Leading sector analysis for strengthening local own-source revenue: Evidence from Pulang Pisau Indonesia - Tuah, Sunaryo N.; Ompusunggu, Dicky Perwira (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
Regional economic development requires accurate identification of strategic sectors that contribute significantly to local revenue. In the context of Indonesia's fiscal decentralization, regional governments are increasingly expected to optimize their economic potential to enhance Regional Own Revenue (PAD). This study aims to identify the leading economic sectors in Pulang Pisau Regency, Central Kalimantan, and examine their influence on PAD from 2010 to 2024. The research adopts a quantitative approach using secondary data sourced from the Central Bureau of Statistics. Four analytical methods are employed to determine leading sectors: Location Quotient (LQ), Shift-Share analysis, Klassen Typology, and Overlay analysis. After identifying leading sectors, multiple linear regression is used to assess their impact on PAD. The results show that two sectors—Agriculture, Forestry, and Fisheries; and Construction—are consistently classified as leading sectors based on their high specialization, competitiveness, and structural contribution. Regression analysis reveals that the Agriculture, Forestry, and Fisheries sector has a significant positive effect on PAD, confirming its strategic role in fiscal development. Conversely, the Construction sector shows a negative and significant effect, suggesting limited fiscal retention and low tax linkage within the local economy. These findings highlight the importance of aligning economic development policies with sector-specific fiscal strategies. The study recommends that regional governments prioritize agricultural sector development through infrastructure, value chain integration, and tax system reform. In contrast, regulatory adjustments are needed in the construction sector to enhance its contribution to local revenue, such as through local content requirements and contractor tax enforcement. Future research should incorporate qualitative dimensions and governance factors to deepen the understanding of PAD performance in decentralized regions